Determination of Minimum Rates for Notary Honorarium to Avoid Tariff War between Notaries - Widya Ishwara Danardana; Maryanto Maryanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The notary position is an institution created by the state. Notary as a position is a field of work created by legal rules for certain functions and is sustainable as a work environment. The existence of a notary as a state official who is authorized to make a legal product, namely an authentic deed, does not receive an honorarium from the state, therefore a notary is entitled to receive an honorarium for the legal services provided. Notaries receive an honorarium from the public for services in making an authentic deed. The honorarium is given to those who carry out their duties based on the laws and regulations, while the success fee is given to those who carry out the profession. Based on this description, This study aims to find out and analyze the basic regulatory considerations related to the amount of the Notary's honorarium in the Notary Position Act and the Notary Code of Ethics, analyze the formulation of the minimum amount of Notary honorarium arrangement, and find out the sanctions for notaries who violate the rules on the minimum rate of Notary honorarium. The research method in this thesis uses a sociological juridical approach with descriptive research specifications. Data sources and data collection methods used primary and secondary data which were analyzed qualitatively. The results of the study indicate that the basis for consideration of setting the minimum amount of notary honorarium in the Law on Notary Positions has not been determined regarding the minimum amount. Basically, the Law on Notary Positions only provides a maximum limit on the honorarium that can be withdrawn from transactions. Notaries have the right to determine their own values based on their considerations as long as they do not exceed the maximum provisions of the Law on Notary Positions. It is necessary to amend Article 36 of the Law on Notary Positions in order to mention the determination of the minimum honorarium limit determined by the notary position organization, so that the determination of the notary position professional organization has binding power based on the Notary Position Act.